2016
DOI: 10.1186/s40064-016-2058-z
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and death after Clostridium difficile infection: gender-dependant influence of proton pump inhibitor therapy

Abstract: GoalsTo determine whether patients with a pre-existing PPI treatment had a higher risk of poor evolution (recurrence or death) when diagnosed with a toxicogenic Clostridium difficile digestive infection.BackgroundPrevious studies identified pump proton inhibitor (PPI) prescription as a risk factor for C. difficile infection. The influence of PPI on the outcome of C. difficile infection is controversial.StudyThis was a retrospective monocentric cohort study. All cases of patients in our center with a symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In total, 18 studies were included for qualitative review and 16 studiesdten caseecontrol studies [15e25] and six cohort studies [3,26e30]dwere included in the meta-analysis. Two studies [31,32] contained insufficient data to calculate a measure of association and results are described qualitatively.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 18 studies were included for qualitative review and 16 studiesdten caseecontrol studies [15e25] and six cohort studies [3,26e30]dwere included in the meta-analysis. Two studies [31,32] contained insufficient data to calculate a measure of association and results are described qualitatively.…”
Section: Search Resultsmentioning
confidence: 99%
“…Two additional studies used metrics other than the odds ratio; in these the crude data were not available. Dos Santos-Schaller et al [31] noted an increased hazard of experiencing the composite outcome of CDI recurrence or death in male patients with preexisting prescription for a PPI (HR 2.32, 95%CI 1.26e4.27). A lower quality study [32] observed that PPI use was correlated with a decreased risk of recurrent CDI on univariate analyses (p 0.0006).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Another is a study that reported male patients with proton pump inhibitor use have a higher risk of CDI mortality. 20 21 Tuberculosis incidence is higher in men in South Africa (male 226 000 vs female 154 000) and a tendency for men to present for healthcare later in their disease course has been reported in South Africa and globally. 22 23 Despite the propensity for CDI-related mortality in men, previous studies in high-resource settings report women are more likely to have CDI.…”
Section: Discussionmentioning
confidence: 99%
“…The search for alternative treatments against CDAD is becoming more and more urgent [16]. TCM has a history of thousands of years, and it has its own unique theory on CDAD.…”
Section: Discussionmentioning
confidence: 99%